Baicalin mitigates alcoholic-associated liver disease via SOCS1-driven reprogramming of macrophages - Sha Huang; Yuhua Wang; Jinjie Wen; Wenjuan Ji; Qiuxiang Zeng; Kaili Deng; Min Li; Shanshan Kuang; Wen Zhang; Mo Chan; Chuying Zhou; Zhiping Lv; et al. (Chinese Medicine)
Abstract Backgrounds Alcoholic liver disease (ALD), a consequence of excessive alcohol consumption, is characterized by high incidence and mortality rates. Presently, there are no effective pharmacological interventions available for the treatment of ALD. Baicalin (BA), a natural flavonoid derived from the root of Scutellaria baicalensis, has exhibited notable hepatoprotective effects. Nevertheless, the mechanisms through which BA influences the interaction between suppressor of cytokine signaling 1 (SOCS1) and macrophages during hepatic immune development remain insufficiently understood. Materials and methods This study seeks to examine the regulatory effects of BA on ALD and to elucidate the relationship between SOCS1 and macrophage differentiation. Our experimental methodology involves the novel application of zebrafish as an in vivo model for ALD. To further investigate the underlying mechanisms, we employed gene knockout and overexpression techniques. Results The study demonstrates that BA substantially alleviates ALD in both in vivo and in vitro settings by upregulating SOCS1 expression in macrophages. Furthermore, we elucidated the association between SOCS1 and macrophage reprogramming. Specifically, SOCS1 knockdown led to the downregulation of CD86, CD80, and iNOS expression, whereas SOCS1 overexpression enhanced the expression of CD206, CD163, IL-4, and IL-10. Conclusion In conclusion, our findings suggest that BA attenuates ALD via the modulation of SOCS1-mediated macrophage reprogramming.